2014
DOI: 10.1097/id.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of the Replaceable Bony Window in Lateral Maxillary Sinus Augmentation

Abstract: This study demonstrates that the replaceable bony window acts as an osteoinductive homologous barrier membrane over various bone graft materials and accelerates new bone formation in lateral sinus augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Despite the presence of residual marginal defects containing adhesive remnants and connective tissue, the bone plates at the test sites appeared to be well incorporated into the newly formed bone within the available area and at the edges of the antrostomy. This is in agreement with retrospective clinical studies (Kim et al, ; Tawil, Tawil, & , Khairallah, A., ) that showed a good incorporation of the bone plate repositioned on the antrostomy both at the surgical inspection and at a CBCT analysis. Also, in an experiment in rabbits previously discussed (Moon et al, ), the bone plate was found incorporated onto the newly formed bone.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Despite the presence of residual marginal defects containing adhesive remnants and connective tissue, the bone plates at the test sites appeared to be well incorporated into the newly formed bone within the available area and at the edges of the antrostomy. This is in agreement with retrospective clinical studies (Kim et al, ; Tawil, Tawil, & , Khairallah, A., ) that showed a good incorporation of the bone plate repositioned on the antrostomy both at the surgical inspection and at a CBCT analysis. Also, in an experiment in rabbits previously discussed (Moon et al, ), the bone plate was found incorporated onto the newly formed bone.…”
Section: Discussionsupporting
confidence: 90%
“…Mean values ± SD and confidence interval of the difference of the means of mineralized new bone and xenograft percentages (%) in the available area and the various region, and of the available area (mm 2 Note. Data of the 3 periods of healing are reported.is in agreement with retrospective clinical studies(Kim et al, 2014;Tawil, Tawil, & , Khairallah, A., 2016) that showed a good incorporation of the bone plate repositioned on the antrostomy both at the surgical inspection and at a CBCT analysis. Also, in an experiment in rabbits previously discussed(Moon et al, 2014), the bone plate was found incorporated onto the newly formed bone.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Unlike collagen membranes, replaceable bony windows act as a homologous osteoinductive barrier; as such, homologous bony windows are free from viral cross-contamination of animal or human origin, and precise adaptation of lateral bony windows completely prevents soft tissue ingrowth. Repositioning of the bony window clinically led to complete bone healing between the replaceable bony window and more mature bone was observed along the floor of the replaceable bony window than at the center of the graft site 3 , 4 . It is time to review and accept change to inflexible views regarding sinus augmentation in order to improve patient outcomes.…”
mentioning
confidence: 96%
“…Because lower rate of mucosal perforation is reported in many studies, PBS is commonly used when crestal and lateral sinus elevation is performed. In addition, the lateral bony window created by the piezoelectric saw insert is repositioned precisely and also acts as an osteoinductive/osteoconductive substrate in the maxillary sinus in bone grafted/non-bone grafted sinus2. On the other hand, collagen barrier has no effect on bone regeneration.…”
mentioning
confidence: 99%